Minimizing Drying Shrinkage and Enhancing Impermeability of Foam Concrete Modified with Epoxy Resin - Jianqing Gong; Ke Li (Advances in Civil Engineering)
Relatively high drying shrinkage and permeability were two of the major challenges associated with foam concrete (FC), primarily due to its high porosity nature. This study was aimed at reducing the drying shrinkage and improving the impermeability of FC by blending and modifying it with epoxy resin (EP). Extensive laboratory testing yielded an optimum content of 4.0% EP, corresponding to a minimum drying shrinkage rate of 1.47 mm/m, which was 48% lower than that of the unmodified FC. At this optimum dosage of 4.0% EP, the permeability pressure was at a maximum level of 1.4 MPa, whereas the permeability coefficient was at its lowest value of 0.75 × 10−9  mm/h. Internal pore structure and EP distribution were characterized using the scanning electron microscopy and indicated that a microgrid structure of the FC was formed internally, featuring an increase in the number of pores, a reduction in the average pore size, and a uniform pore size distribution. Similarly, surface energy measurements using the tensiometry method yielded maximum surface energy values at 4.0% EP content, which could be used to explain the reduced drying shrinkage and the enhanced impermeability characteristics of the modified FC.